Inhibition of TGF-β-Smad signaling attenuates hyperoxia-induced brain damage in newborn rats - Zhang, Ting (Int J Clin Exp Pathol, 2019)
Transforming growth factor-beta (TGF-β) is ubiquitously expressed in various tissues and functions in pathologic processes, including hyperoxia. In the present study, we investigated the expression and functional role of TGF-β in brain tissue during hyperoxia-induced brain damage. Three days old neonatal rats were treated with hyperoxic conditions (80% O(2)) for 7 days, followed by TGF-β, Smad, and MAPK detection by western blotting and immunohistochemical staining. The functional role of TGF-β was assessed by treating hyperoxic neonatal rats with neutralizing antibody against TGF-β and caffeine, followed by histological and myelin basic protein (MBP) staining. Our results demonstrated upregulation of TGF-β and activation of the Smad/MAPK signaling pathway in brain tissue of neonatal rats under hyperoxic conditions. Injection of neutralizing antibody against TGF-β efficiently blocked TGF-β expression, accompanied by inactivation of the Smad/MAPK signaling pathway. Further evidence confirmed the attenuation of hyperoxia-induced brain damage by a neutralizing antibody against TGF-β in neonatal rats. Similar attenuation was also observed for caffeine. Collectively, our results indicate that TGF-β is a therapy target for hyperoxia-induced brain damage in neonates.